DAMPAK DANA OTONOMI KHUSUS TERHADAP TINGKAT PERTUMBUHAN INDEKS PEMBANGUNAN MANUSIA DI PROVINSI ACEH - Nasril Isnadi; Fikriah Fikriah (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract This study aims to determine how much the impact and analysis of the special autonomy fund received by Aceh Province on the growth of the Human Development Index. This research focuses on the development and projection of HDI in line with the existence of special autonomy funds received from the central government to the Aceh government from 2008. The types of data used in this study are secondary data in the form of times series from 1996 - 2018. Data analysis methods used this research is trend liner square. The results showed that the Aceh Province HDI Value from 1996 to 2016 where the data was divided into 2 linear trends, namely before the DOK from 1996 - 2008 with the equation model Y = 0.5823x - 2.0954. While the linear trend after the DOK is from 2008 - 2016, namely Y = - 0.1888x + 2.2329. Based on the results of multiple linear regression analysis where the results of the analysis show that the DOK is not significant towards the growth of the human development index (HDI).Keywords:HDI, DOK